Religiosity and ethical business behavior: A Study on differences between catholic and protestant students - Giacomin, Olivier; Gundolf, Katherine; Shinnar, Rachel; Janssen, Frank; Saroglou, Vassilis (Management international / International Management / Gestiòn Internacional, 2025)
Research has sought to better understand the antecedents of ethical decision-making, especially in businesses. Yet, researchers found no clear relationship between religion or religiosity and ethics. This study contributes to research on religiosity and ethics by examining the impact of religiosity on business ethics among university students. Using a sample of Protestant and Catholic students, we investigate how individual religiosity shapes perceptions of three unethical behaviors: misuse, exchange of favors, and deceit. Findings show that individual religiosity matters in how different scenarios of unethical conduct are perceived. We identify similarities and differences between Protestant and Catholic individuals depending on ethical behavior.